2002
DOI: 10.1074/jbc.m108025200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Differentially Regulates Cell Cycle Progression in X-transforming Versus Nontransforming Hepatocyte (AML12) Cell Lines

Abstract: Hepatitis B virus (HBV) X protein (pX) is implicated in Epidemiological evidence (1) links chronic hepatitis B virus (HBV)1 infection in humans to development of hepatocellular carcinoma (HCC). Evidence derived from comparative studies of mammalian and avian hepadnaviruses, transgenic animal studies, and cell culture transformation studies collectively (2, 3) support a role for the 16.5-kDa HBV X protein (pX) as a weak oncogene, implicated in HCC development. However, the mechanism(s) by which pX effects hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 84 publications
5
85
0
Order By: Relevance
“…2). Furthermore, it is unclear how centrosome overduplication or a defect in the mitotic checkpoint would lead to the prolonged S-phase that we and others 18,24 observe on HBx expression, nor does it easily explain the high occurrence of lagging chromosomes in mitotic cells showing normal bipolar spindles (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Furthermore, it is unclear how centrosome overduplication or a defect in the mitotic checkpoint would lead to the prolonged S-phase that we and others 18,24 observe on HBx expression, nor does it easily explain the high occurrence of lagging chromosomes in mitotic cells showing normal bipolar spindles (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] We further show that, unexpectedly, despite causing multiple mitotic defects, HBx neither prevents bipolar spindle cells from proceeding normally through mitosis nor impairs the mitotic spindle checkpoint, but instead delays cells in S-phase because of activation of the DNA replication checkpoint. The use of an HBx point mutant, HBx(R96E), that is specifically impaired for DDB1 binding 9 showed that all these events are dependent on HBx interacting with DDB1, thus suggesting a causal link and providing an explanation for the DDB1-binding dependent cytotoxic activity of HBx reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, HBx-induced multinucleated cells under microtubule-damaging conditions (Lee et al, 2002) could be potentially mediated through defects in the mitotic checkpoint. To examine this possibility, we first used a targeted yeast two-hybrid assay to detect binding between HBx and any of the MCC components.…”
Section: Hbx Targets Hbubr1mentioning
confidence: 99%
“…HBx is a multifunctional protein (Murakami, 2001), which deregulates cell cycle checkpoint controls (Madden and Slagle, 2001) potentially including the G 2 /M checkpoint (Lee et al, 2002). Notably, HBx-expressing cells become multinucleated under microtubule-damaging conditions (Lee et al, 2002), raising the possibility of mitotic checkpoint defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation